The role of organic acids in the uptake and storage of nickel in hyperaccumulator plant, Brackenridgea palustris ssp. foxworthyi (Elm.) P.O. Karis - Maria Ellenita Gibe De Castro; Marissa A Noel; Jose Santos R Carandang VI (Brawijaya University, 2020)
The role of low molecular weight organic acids (LMWOAs) in the Philippine nickel (Ni) hyperaccumulating plant, Brackenridgea palustris ssp. foxworthyi (Elm.) P.O. Karis is not yet fully understood. Using High Performance Liquid Chromatography (HPLC), the presence of organic acids such as oxalic, citric and malic acids were determined. Average nickel concentration in the plant tissues followed the ascending order: roots>stem>leaves with values of 7,294.73 µg/g, 7,412.30 µg/g and 9,866.46 µg/g, respectively. Among the organic acids analyzed, only oxalic acid was detected in all the plant tissues at considerable concentration. Linear correlation between oxalic acid and Ni concentrations in 0.025 M HCl plant extracts generated a positive r-value of 0.0437 indicating that as Ni content increases, oxalic acid also increases. This paper suggests that oxalic acid can be synthesized by B.palustris ssp. foxworthyi, therefore, it may acts as a ligand that chelates Ni and other metals to the aboveground tissues were it gets compartmentalized. To our knowledge, this will be the first report on the presence of organic acids in the Philippine endemic Ni hyperaccumulator plant, B. palustris ssp. foxworthyi whose potential was discovered more than thirty (30) years ago.